Learning science : the value of crafting engagement in science environments - Schneider, Barbara L.; Krajcik, Joseph S.; Lavonen, Jari; Salmela-Aro, Katariina (Yale University Press, 2020)
An innovative, internationally developed system to help advance science learning and instruction for high school students This book tells the story of a